Priest & parish in eighteenth-century France : a social and political study of the curés in a diocese of Dauphiné, 1750-1791 - Tackett, Timothy, 1945- (Princeton legacy library, 1977)
This book provides a comprehensive collective biography of the parish priests in one diocese--their origins, education, and careers: their relationship with their parishioners; and the process by which they were politicized prior to 1789. The author's analysis uses both quantitative and more traditional historical techniques. Originally published in 1977. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.